Understanding the Role of Human Resource Attributions in Shaping Employee Creativity: A Qualitative Study of Hotel Employees in Yogyakarta - setiono, Agus; Nazmah, Nazmah; Ayu, Ade Rahma (Universitas Pamulang, 2025)
This study aims to explore how hotel employees in Yogyakarta interpret human resource management (HRM) practices and how these perceptions influence their creativity at work. Using the concept of HR attributions, it examines the personal and organizational meanings employees assign to HR efforts and their impact on creative behavior. Data were collected through semi-structured interviews with 20 hotel employees. Thematic analysis revealed that both individual factors, such as motivation and personal values, and organizational factors, including leadership support and team culture, shape employees’ creativity. Findings indicate that employees’ perceptions of the sincerity and relevance of HR practices significantly affect their willingness to innovate beyond formal roles. This research offers valuable insights for future studies on the emotional and contextual aspects of HRM and creativity, particularly in service industries like hospitality.